Socially aware organisations and technologies : impact and challenges : 17th IFIP WG 8.1 International Conference on Informatics and Semiotics in Organisations, ICISO 2016, Campinas, Brazil, August 1-3, 2016, proceedings /: impact and challenges : 17th IFIP WG 8.1 International Conference on Informatics and Semiotics in Organisations, ICISO 2016, Campinas, Brazil, August 1-3, 2016, proceedings. (2016) - Unknown
No abstract available